Global Substrate Mapping and Targeted Ablation with Novel Gold-tip Catheter in De Novo Persistent AF - Michael TB Pope; Timothy R Betts (Arrhythmia & Electrophysiology Review)
Results from catheter ablation for persistent AF are suboptimal, with no strategy other than pulmonary vein isolation showing clear benefit. Recently employed empirical strategies beyond pulmonary vein isolation involve widespread atrial ablation in all patients and do not take into account patient-specific differences in AF mechanisms or phenotype. Charge density mapping using the non-contact AcQMap system (Acutus Medical) allows visualisation of whole-chamber activation during AF and reveals localised patterns of complex activation thought to represent important mechanisms for AF maintenance that can be targeted with focal ablation. In this review, the authors outline the fundamentals of this technology, the initial data exploring the mechanistic role of activation patterns seen and the application to ablation of persistent AF.